The effects of digital games on student's learning experience: a review of literature / Mahathir Mahali ...[et al.] - Mahali, Mahathir; Jamaluddin, Junaidah; Mohd Din, Norlaila; Ahmad, Mohamad Azmi Nias; Abdul Jabar, Faizan; Mohamad Fadzillah, Nur Syazwani (2016)
Today digital games have become an important part of "digital generation" who have grown up playing computer and video games and increasingly an important part of our culture as a whole. Despite many criticisms, there is now increasing interest in asking whether digital games might be offering a powerful new medium to support student's learning in the information age. Researchers and educators have started researching on how to apply games into classroom activities to foster and support the learning process. The purpose of this paper is to discuss the effects of digital games on student's learning based on a review of literature. Many of the researchers focus their attention on the effects of the games on student's motivation, enjoyment, interest, skills, academic performance, competitiveness, efficacy, teamwork, attitude, psychology and health. In addition, this paper will also highlight some of the barriers and challenges in using digital games within our current education system and within our existing modes of learning.